Manajemen Pembinaan Olahraga Sepaktakraw Di PSTI Kabupaten Purworejo Tahun 2019 (Universitas Negeri Semarang, 2021)
This research conducted to know the coaching management of Sepaktakraw in PSTI Purworejo Regency on 2019. This study belonged to qualitative descriptive approach. The method to collect the data were observation, interviews, and documentation. This research conducted atthe PSTI Secretariat, Purworejo Regency, KHA Dahlan street No.10, Purworejo District, Purworejo Regency, Jawa Tengah. The subjects of this research were administrators, coaches, and athletes. The data analysis in this study uses 3 interconnected components, namely data reduction, data presentation, and conclusion drawing. The results which obtained in this study were:1) The first management function is planning, as a whole it has not been going well because there are still many shortcomings such as no short, medium, long term planning and unclear characteristics of the training program. 2) The second management function is organizing, the implementation has not been carried out well, all management still have to improve their performance and actively support the smoothness and progress of Sepaktakraw coaching in Purworejo Regency. 3) The third management function is leadership, it has been running quite well according to the program made by the management and the trainer, although the current training program is still unclear. 4) The fourth management function is supervision, the Sepaktakraw PSTI Purworejo Regency achieved good progress and potential athletes have started to emerge. The conclusion of this research are that the planning and organizing of the Sepaktakraw coaching management in PSTI Purworejo Regency on 2019 has not been carried out well, while the leadership and supervision have been running quite well.